Problems and difficulties of the Philippine Normal College in off-campus teaching - Parfan, Aurea G. 1907- (1955)
The problems in off-campus teaching of the Philippine Normal College was investigated in this study. The study was limited to the most common and difficult problems encountered by: the regular student teachers in their off-campus practice teaching, the BSE interns in their internship training in cooperating schools, the cooperating teachers in guiding and directing students teaching in their own schools, and the administration in its implementation of the program of off-campus student teaching of Philippine Normal College student teachers.